AnMas: Anisotropic strength domain for masonry. (15th April 2022) - Malena, Marialaura; de Felice, Gianmarco; Marfia, Sonia
Abstract: A new orthotropic limit function is developed to describe the failure of masonry under in-plane loads. The formulation starts from the isotropic smooth 3D yield function proposed by Bigoni and Piccolroaz (2004) to provide a strength condition for masonry through a single analytical function including orthotropy and different tensile and compressive strengths. The material parameters are calibrated by means of a simple optimization procedure based on available experimental and numerical data. Finally, the limit function is implemented in a finite element code in the framework of a perfect plasticity, through a numerical procedure based on a predictor–corrector algorithm. The effectiveness of proposed model is verified through the comparison of numerical simulations with experimental data available in the literature. Highlights: The new orthotropic limit function AnMas for masonry has been developed. A simple optimization procedure is adopted for the calibration of the new function. The limit function takes into account the orientation of the mortar bed joints. The limit function can be easily and successfully implemented as yield function in a plastic model for masonry.